STUDENTS’ PERCEPTION OF ENGLISH TEACHERS’ TEACHING STYLES AND THEIR INFLUENCE ON STUDENTS INTEREST IN THE LEARNING PROCESS - Ramadhani, Trecy Trinita; Korompot, Chairil Anwar; Samtidar, Samtidar (State University of Makassar, 2025)
This study aims to explores students' perceptions of their English teachers' teaching styles and their influence on students’ interest. Conducted among Sophomore and General classes at My Liberty English Course, the research used a descriptive quantitative approach with a survey design. A questionnaire captured students' views on teaching styles and their influence on student interest. The findings indicate that students have varying preferences for different teaching styles, with a notable appreciation for the Expert and Delegator styles. These styles were associated with higher levels of student engagement and interest. Other styles, such as Personal Model and Formal Authority, also received positive feedback, while the Facilitator style was less favoured. The study concludes that specific teaching styles significantly influence students' attention, willingness, needs, feelings of happiness, participation, and overall attitude toward learning English.Keywords: Perception, Teaching Styles, Students Interest